Propagation multimodale dans les systèmes périodiques couplés - Mencik, Jean-Mathieu; Ichchou, Mohamed; Jézéquel, Louis (European Journal of Computational Mechanics, 2006)
This paper presents the study of the wide band vibratory behavior of coupled elastic and dissipative complex periodic systemseach system is composed, along a specic direction, of identical substructures. Considering a multi-mode propagation model, the dynamics of each system is formulated by numerically expressing the kinematic variables (displacements, forces) from the waves propagating along the direction of periodicity. In this way, a coupling model for several systems connected by an elastic element, which in particular can be submitted to external excitation sources, is formulated.